A simplified procedure for the subtractive cDNA cloning of photoassimilate-responding genes: Isolation of cDNAs encoding a new class of pathogenesis-related proteins - Sonnewald, Uwe; et al. (Plant Molecular Biology, 1995)
Transgenic tobacco plants (ppa-1) constitutively expressing Escherichia coli pyrophosphatase behind the 35S CaMV promoter accumulate high levels of soluble sugars in their leaves [27]. These plants were considered a tool to study adaptation of leaves to photoassimilate accumulation at the molecular level. By differential hybridization of a subtractive library enriched for transcripts present in the transgenic plants 12 different cDNAs were isolated. By sequence analysis four cDNAs could be identified as 1-aminocyclopropane-1-carboxylate-oxidase and as three different pathogenesis-related proteins (PR-1b, PR-Q and SAR 8.2). Two cDNAs were homologous to a calmodulin-like protein from Arabidopsis and a human ribosomal protein L19 while six cDNA clones remained unknown. One of these clones (termed PAR-1 for photoassimilate-responsive) displayed features similar to pathogenesis-related proteins: Hybridizing transcripts, 1.2 and 1.0 kb in length, were strongly inducible by salicylate and accumulated in tobacco plants after infection with potato virus Y (PVY) both in infected and uninfected systemic leaves. PAR-1 transcripts also accumulated in wildtype leaves upon floating on glucose and sucrose whereas sorbitol and polyethylene glycol had no effect. Rescreening of the ppa-1 cDNA library with the PAR-1 cDNA as probe resulted in 25 hybridizing cDNAs which by homology were found to fall into three classes (PAR-1a, b, c). The cDNAs coding for PAR-1a and b were 90.6% homologous on the DNA level while both were less related to the PAR-1c cDNA (70.5% and 75.2% homologous, respectively). One open reading frame was identified in all three PAR-1 cDNA classes. Translation would result in proteins with a theoretical molecular mass of about 20 kDa. The N-terminal amino acid sequences resemble a signal peptide which would direct the proteins to the secretory pathway. Using selective 3' hybridization probes of the three PAR-1 cDNAs it was possible to discriminate the different transcripts. Both PAR-1a and PAR-1c mRNAs are induced in plants treated with PVY.
Keywords: gene regulation; pathogenesis-related proteins; potato virus Y; subtractive cDNA library; sugar accumulation; transgenic tobacco plants